Genotyping, Assessment of Virulence and Antibacterial Resistance of the Rostov Strain of Mycobacterium tuberculosis Attributed to the Central Asia Outbreak Clade - Mikhail V. Fursov; Egor A. Shitikov; Julia A. Bespyatykh; Alexander G. Bogun; Angelina A. Kislichkina; Tatiana I. Kombarova; Tatiana I. Rudnitskaya; Natalia S. Grishenko; Elena A. Ganina; Lubov V. Domotenko; Nadezhda K. Fursova; Vasiliy D. Potapov; et al. (Pathogens, 2020)
The Central Asia Outbreak (CAO) clade is a growing public health problem for Central Asian countries. Members of the clade belong to the narrow branch of the Mycobacterium tuberculosis Beijing genotype and are characterized by multidrug resistance and increased transmissibility. The Rostov strain of M. tuberculosis isolated in Russia and attributed to the CAO clade based on PCR-assay and whole genome sequencing and the laboratory strain H37Rv were selected to evaluate the virulence on C57Bl/6 mice models by intravenous injection. All mice infected with the Rostov strain succumbed to death within a 48-day period, while more than half of the mice infected by the H37Rv strain survived within a 90-day period. Mice weight analysis revealed irreversible and severe depletion of animals infected with the Rostov strain compared to H37Rv. The histological investigation of lung and liver tissues of mice on the 30th day after injection of mycobacterial bacilli showed that the pattern of pathological changes generated by two strains were different. Moreover, bacterial load in the liver and lungs was higher for the Rostov strain infection. In conclusion, our data demonstrate that the drug-resistant Rostov strain exhibits a highly virulent phenotype which can be partly explained by the CAO-specific mutations.